STRUKTUR PERTUNJUKAN WAYANG KULIT LAKON KRESNA DUTA GAYA YOGYAKARTA SAJIAN HADISUGITO - Andi Wicaksono (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2021)
This article discusses the structure of Kresna Duta's shadow puppet show. The theoritical perspectives applied in this article are; the theory of Yogyakarta style shadow puppet performance structure by Mudjanattistomo (1977), and the theory of jejer classification by Wahyudi (2013). The term“jejer” refers to the episodes grouping based on some occassions that happen in the same territory. These two methods are suitably used for the narration analysis, the decissions taken and the behaviour of the character, as well as the phenomenon within the story. The results of these methods show that the story of Kresna Duta performed by Ki Hadi Sugito consist of thirty four episodes which are then classified into seven jejer (seven episodes grouping). There are two types of episodes grouping which are found in the story of Kresna Duta structure, they are; (1) jejer gendhing and jejer gladhagan. This article is one part of the previous study of “Pandhawa Sahaya Dalam Lakon Kresna Duta Sajian Ki Hadi Sugito: Analisis Hermeneutik Tokoh Kresna Gaya Yogyakarta Hadi Sugito”.